Endometriosis in the hypogastric nerve (Research, Society and Development, 2022)
Introduction: Endometriosis is defined as the presence of endometrial tissue outside the uterine cavity, thus generating numerous symptoms for the patient. The pathology can affect neurologically essential regions, such as the Hypogastric Nerve. Objective: The study seeks to present aspects of endometriosis, and analyze its relationship to the hypogastric nerve. Methodology: As an instrument used to obtain bibliographic data on the subject, the following databases were consulted: Scielo; Medline; PubMed; Virtual Health Library (VHL), in the period comprising the last 10 years. Results and discussions: From this perspective, when endometriosis involves and affects the nerves, a condition called neuropathy develops. The hypogastric nerve, in turn, divides into an abdominal branch and a genital branch. Thus, according to the evolution of the involvement, such regions begin to report greater discomfort. Therefore, efficient, fast and safe treatment and diagnosis is necessary, with the support of a multidisciplinary team and full patient participation. Conclusion: It is understood, therefore, that endometriosis, especially of the hypogastric nerve, ends up requiring a faster intervention, since neurological lesions can develop.